Analysis of stress state of the contact system «disk-blade» - Burago, Nikolay Georgievich; Zhuravlev, Alexey Borisovich; Nikitin, Iliya Stepanovich (Computational Continuum Mechanics, 2011)
In this paper we present a mathematical model of the system disk-blade of a gas-turbine engine (GTE), which takes into account centrifugal forces, distributed aerodynamic loads and nonlinear contact conditions. The influence of centrifugal and aerodynamic forces and contact conditions on formation of stress concentration zones near the disk and blade junction is studied numerically.
Keywords: stress concentration; mathematical model; GTE disk; centrifugal forces; distributed aerodynamic loads; nonlinear contact conditions